2009
DOI: 10.1080/03602550802674556
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polyurethane-Based Sheets by Coagulation Method and Study of Mechanical and Cushion Properties for Therapeutic Footwear Applications

Abstract: Many foams and viscoelastic materials are used in shoes as insoles to replace the shock-absorbing and pressure distributing functions of natural fat pad beneath the foot that was lost due to some conditions such as diabetes, arthritis, age or overuse. In the present work, porous polyurethane sheets of 3-10 mm thickness based on segmented polyetherurethanes and polyesterurethane were developed by coagulation method. Sheets of different density, hardness and thickness were developed and tested for their mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Tensile and tear strength are typically analysed for insole materials. For the insole materials demonstrating CE greater that 70 N•mm and CF 4-8, the typical value of tensile strength is 0.7-1.05 MPa (Saraswathy et al 2009), again overlaps with the values for Poron® (0.53-1.38 MPa) and Sorbothane® (0.75-1.2 MPa).…”
Section: Optimal Characteristics For Insolesupporting
confidence: 62%
See 1 more Smart Citation
“…Tensile and tear strength are typically analysed for insole materials. For the insole materials demonstrating CE greater that 70 N•mm and CF 4-8, the typical value of tensile strength is 0.7-1.05 MPa (Saraswathy et al 2009), again overlaps with the values for Poron® (0.53-1.38 MPa) and Sorbothane® (0.75-1.2 MPa).…”
Section: Optimal Characteristics For Insolesupporting
confidence: 62%
“…Investigation of PUF performance in conditions of applied static pressure was carried out on the second step since compression set (CS) is a crucial characteristic of insole material. All samples were studied at the room temperature (23°C) according to SATRA TM 64 method as described by Saraswathy et al (2009) and at the elevated temperature (40°C). The phenomena of PUF softening at the temperature close to the body temperature was described by Shariatmadari et al(2012) and possible change in FSR sensors output (North et al 2010) necessitate to conduct a similar test as described in SATRA TM 64, but at a higher temperature.…”
Section: Compression Setmentioning
confidence: 99%
“…Ismail et al [37] observed that the hardness of natural rubber composite increased with increasing of filler loading of bamboo fiber from 35 to 65 varying the filler loading (phr) from 0 and 50.…”
Section: Resultsmentioning
confidence: 99%
“…High molecular weight polyester urethanes sheets showed Shore A hardness values in the range of 25-33 which were grouped as hard materials. It was considered that the increase in hardness was due to the increase of polymer concentration and higher molecular weight of polyurethanes [28]. Ferrite-natural rubber composite exhibited a disposition to Shore hardness increase with increasing filler content from 37 to 44 varying the filler loading (phr) from 0 and 120 [29].…”
Section: Resultsmentioning
confidence: 99%